Kierunki inwestycji polskich przedsiębiorstw na Ukrainie - Rybka, Wiktor (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The economic reforms and the process of opening Ukraine to the world have facilitated the inflow of foreign investment. The author presents statistics (FDI) showing the continuous flow of Polish capital to the Ukrainian economy. The statistics also show that the majority of the Polish capital has been applied to the industrial sector of the Ukrainian economy. Recent press reports on the volume of Polish enterprises' investments in Ukraine suggest their dynamic increase in 2007. The aim of this article is to present the trends in Polish enterprises' investments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 566-576